Early text page alarms sent to cardiologists reduce door-to-balloon times in ST-elevation myocardial infarction. (July 2014) - Park, Jin-Kyu; Kim, Seok Hwan; Shin, Jeong Hun; Shin, Jinho; Kim, Kyung-Soo; Lim, Young-Hyo
We assessed an early notification system using smartphones to reduce door-to-balloon times (DTBT) in ST-elevation myocardial infarction (STEMI). Text page alarms were sent to cardiologists for all patients presenting with chest pain or an equivalent in the emergency department before acquisition of an electrocardiogram (ECG). A total of 210 patients (with mean age of 59 years) were investigated (109 in the intervention group and 101 in a control group from the previous two-year period). The primary outcome, the DTBT, was significantly lower in the intervention group compared to the control group (55.0 and 92.5 min, respectively, P  < 0.001). In a secondary analysis, the length of hospital stay was also significantly less. However, there was no significant improvement in all-cause one-year mortality. Early text page alarms using smartphones were effective in reducing the DTBT, but had a limited effect on clinical outcome.